2021
DOI: 10.3390/su13020743
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and Acquisitions within the Sharing Economy: Placing All the Players on the Board

Abstract: The sharing economy is changing the way customers perceive businesses and making traditional companies face new challenges. Many outmoded companies have decided to embrace these changes either by creating their own sharing platforms or by acquiring an already existing one. This paper is an initial attempt to shed light on the reasons behind mergers and acquisitions involving at least one sharing platform. We conduct an in-depth analysis of M&As over the period 2012–2019 with a sample of 108 operations, cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…A recent study conducted in a similar context on green M&As in Chinese and Taiwanese contexts has reported the significant influence of such strategies on brand innovations, organizational performance, and cross-border success ( Lu, 2022 ). Another recent research on strategic green marketing and the role of M&As strategy in the Taiwanese context reported that some external factors such as financial advisory may affect the M&As strategy and green marketing approach relationships ( Zhu et al, 2002 ; Pérez-Pérez et al, 2021 ). Such results encouraged the authors to examine the associations conceptually under investigation in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study conducted in a similar context on green M&As in Chinese and Taiwanese contexts has reported the significant influence of such strategies on brand innovations, organizational performance, and cross-border success ( Lu, 2022 ). Another recent research on strategic green marketing and the role of M&As strategy in the Taiwanese context reported that some external factors such as financial advisory may affect the M&As strategy and green marketing approach relationships ( Zhu et al, 2002 ; Pérez-Pérez et al, 2021 ). Such results encouraged the authors to examine the associations conceptually under investigation in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DiDi acquired Uber China in 2016, contributing to its dominating role in China. Such acquisitions or mergers play a large role for unicorn companies (Rowley, 2019) and represent a unique dynamic inherent to the new economy (Jia et al, 2020; Pérez‐Pérez et al, 2021). The later analysis explores how this acquisition activity may have helped in the sharing economy platforms' journeys toward institutionalization.…”
Section: Description Of Case Study Companies and Their Industrymentioning
confidence: 99%
“…Regardless of this empirical challenge, many studies point out an interesting commonality among these firms. Specifically, most sharing economy businesses are innovative, as evidenced by the high number of patents and significant intellectual property valuations, and are the most active participants in the M&A market (Batool et al 2020;Pérez-Pérez et al 2021). This positive link between corporate technological activities (or R&D) and M&As is the most prevalent phenomenon that sharing economy firms exhibit and thus must be thoroughly examined.…”
Section: Mandas In a Sharing Economy And Randdmentioning
confidence: 99%